2012
DOI: 10.1021/bm2015834
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Hybrid Dextrin Hydrogel Encapsulating Dextrin Nanogel As Protein Delivery System

Abstract: Dextrin, a glucose polymer with low molecular weight, was used to develop a fully resorbable hydrogel, without using chemical initiators. Dextrin was first oxidized (oDex) with sodium periodate and then cross-linked with adipic acid dihidrazide, a nontoxic cross-linking molecule. Furthermore, a new bidimensional composite hydrogel, made of oxidized dextrin incorporating dextrin nanogels (oDex-nanogel), was also developed. The oDex hydrogels showed good mechanical properties and biocompatibility, allowing the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 52 publications
0
85
0
Order By: Relevance
“…Cytotoxicity, is defined as the "in vitro evaluation of toxicological risks of a material using cell culture". 46 Cytotoxicity assay is used to investigate in vitro biocompatibility of materials intended to be used for drug delivery application. This is a useful tool to scrutinize a material for in vivo application.…”
Section: Resultsmentioning
confidence: 99%
“…Cytotoxicity, is defined as the "in vitro evaluation of toxicological risks of a material using cell culture". 46 Cytotoxicity assay is used to investigate in vitro biocompatibility of materials intended to be used for drug delivery application. This is a useful tool to scrutinize a material for in vivo application.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that nanogel-embedded hydrogel composites could improve the kinetic release profi le of the drug by affording a nanoscale reservoir barrier, which reduced or even removed the burstrelease effects of drugs in hydrogel or nanogel drug-delivery systems. [ 38,39 ] We envisioned that incorporating periodateoxidized cholesterol-containing dextran (OCDEX) nanogels as drug carriers in a hydrogel would improve the formulation and make it more suitable for drug delivery. As a chemical crosslinker, the aldehyde group-bearing OCDEX nanogel should react with the amino-bearing polysaccharide/polypeptide 4. c) Drug-loaded hydrogels were formulated by the ionic crosslinking of negatively charged PPLG with positively charged polysaccharide/ polypeptide composites (HPCS/PPLL) and the simultaneous Schiff-base reaction between amino-containing HPCS/PPLL complexes and aldehyde group-bearing nanogels containing IL-2, IFN-γ and DOX.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Molinos, M, Carvalho V, et al, 2012. Development of a hybrid dextrin hydrogel encapsulating dextrin nanogel as protein delivery system.…”
Section: Referencesmentioning
confidence: 99%